High interest rates and inflation in the U.S. A reply - FAND, D.I. (PSL Quarterly Review, 2013)
In this brief note the author responds to J.L. Lucia’s criticism regarding the role of expectations in analysing the interest rate escalation in the U.S. in the latter half of the 1960s. JEL: E31, E43